40th Solid Mechanics Conference - Mech, 40th Sol (Engineering Transactions, 2015)
The Solid Mechanics Conferences have been organized by the Institute of Fundamental Technological Research since 1953. The Conferences have served as a forum for the exchange of ideas and research information. The aim of the Conference is to bring together researchers from different countries and to create for them the possibility for the presentation and discussion of scientific results from a wide area of solid mechanics.